Why do entrepreneurial mHealth ventures in the developing world fail to scale? - Sundin, Phillip; Callan, Jonathan; Mehta, Khanjan (Journal of Medical Engineering & Technology, 2016)
Telemedicine is an increasingly common approach to improve healthcare access in developing countries with fledgling healthcare systems. Despite the strong financial, logistical and clinical support from non-governmental organisations (NGOs), government ministries and private actors alike, the majority of telemedicine projects do not survive beyond the initial pilot phase and achieve their full potential. Based on a review of 35 entrepreneurial telemedicine and mHealth ventures, and 17 reports that analyse their operations and challenges, this article provides a narrative review of recurring failure modes, i.e. factors that lead to failure of such venture pilots. Real-world examples of successful and failed ventures are examined for key take-away messages and practical strategies for creating commercial viable telemedicine operations. A better understanding of these failure modes can inform the design of sustainable and scalable telemedicine systems that effectively address the growing healthcare disparities in developing countries.
Keywords: Telemedicine; business models; community health workers; failure modes; global health; mHealth